Tv Football Commentary of Indonesia U23 Against South Korea U23 Match - Janriko Abdussalam Sadiq (Passage, 2018)
This qualitative study examines lexical and syntactic features in a commentary of Indonesia U23 against South Korea U23 match. Elan 5.2 software was utilised to identify the features. The data were analysed using Lakoff and Johnson’s (2003) metaphor and Ferguson’s (1983) syntactic features. The results show that there are three types of lexical features: structural, orientational, and ontological metaphors and five types of syntactic features: simplification, inversion, result expression, heavy modifiers, and routines that are deployed in the commentary of the match. The findings show that syntactic features were used mainly to save utterance time, while lexical features were used as analogy for other concepts. The findings suggest that this study affirms to ideas of using metaphor that football is war and omitting subject, or predicator, or object in commentaries. In addition, in Indonesian context, there is a kind of simplification, that is subject plus predicator plus object deletion in an utterance, and there are only two patterns of result expression: noun phrase and verb construction. Keywords: lexical features, syntactic features, football commentary